Asthma control in Europe: a real-world evaluation based on an international population-based study. - Cazzoletti, Lucia; Marcon, Alessandro; Janson, Christer; Corsico, Angelo, G.; Jarvis, Deborah; Pin, Isabelle; Accordini, Simone; Almar, Enrique; Bugiani, Massimiliano; Carolei, Adriana; Cerveri, Isa; Duran-Tauleria, Enric; et al. (Journal of Allergy and Clinical Immunology, 2007)
International audience BACKGROUND: Epidemiologic evidence related to asthma control in patients from the general population is scanty. OBJECTIVES: We sought to assess asthma control in several European centers according to the Global Initiative for Asthma (GINA) guidelines and to investigate its determinants. METHODS: In the European Community Respiratory Health Survey II (1999-2002), 1241 adults with asthma were identified and classified into inhaled corticosteroid (ICS) users and non-ICS users in the last year. Control was assessed in both groups by using the GINA proposal (controlled, partly controlled, and uncontrolled asthma), and it was related to potential determinants. RESULTS: Only 15% (95% CI, 12% to 19%) of subjects who had used ICSs in the last year and 45% (95% CI, 41% to 50%) of non-ICS users had their asthma under control; individuals with uncontrolled asthma accounted for 49% (95% CI, 44% to 53%) and 18% (95% CI, 15% to 21%), respectively. Among ICS users, the prevalence of uncontrolled asthma showed great variability across Europe, ranging from 20% (95% CI, 7% to 41%; Iceland) to 67% (95% CI, 35% to 90%; Italy). Overweight status, chronic cough and phlegm, and sensitization to Cladosporium species were associated with poor control in ICS users. About 65% and 87% of ICS users with uncontrolled and partly controlled asthma, respectively, were on a medication regimen that was less than recommended by the GINA guidelines. CONCLUSION: Six of 7 European asthmatic adults using ICSs in the last year did not achieve good disease control. The large majority of subjects with poorly controlled asthma were using antiasthma drugs in a suboptimal way. A wide variability in asthma control emerged across Europe. CLINICAL IMPLICATIONS: Greater attention should be paid to asthma management and to the implementation of the GINA guidelines.